Florística de espécies arbóreas no setor básico da Universidade Federal do Pará, Belém, Pará, Brasil - SILVA, Bruno Quaresma (2019)
The floristic survey is a methodology performed to list and diagnose a number of existing plant species in a geographic area. Floristic studies, besides generating information on the taxonomic classifications of individuals in a plant community, provide basic information on ecological attributes, dispersion syndromes, phenology and the life forms of these organisms, as well as other purposes. The present study had as objective to sample and identify the tree species of the Basic Campus Cidade Universitária José da Silveira Netto of the Federal University of Pará. The study took place from January to June 2019. For the floristic survey, weekly collections of botanical material were carried out, using the usual techniques of collection and afforestation. For the taxonomic identification of the species, specific bibliography was used, possible expert consultations and comparisons with exsicates of the H.F Prof. Herbarium. Normélia Vasconcelos of the Federal University of Pará. In total, 787 individuals were cataloged, distributed in 28 families, 74 genera and 85 species. The family that presented the greatest wealth was Fabaceae (18 species), followed by Arecaceae (15) and Bignoniaceae (5). Anacardiaceae showed greater abundance (205 individuals), followed by Bignoniaceae (129), Fabaceae (117) and Arecaceae (87). The Fabaceae family presents more genera (16) and species (18). The genus Mangifera has only one species (Mangifera indica L), however, it has the highest abundance (186). The genus Syzygium contained the fifth largest number of individuals (33) and presented higher species richness (5).